PENGARUH BELANJA MODAL, INVESTASI, DAN NET EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI PULAU SUMATERA: (Studi Kasus 10 Provinsi di Pulau Sumatera Tahun 2011-2014) THE INFLUENCE OF CAPITAL EXPENDITURE, IN - Mega Hartika (EKPI 16 UMY 040, 2016)
*40 This research aims to analyze the influence of capital expenditure, investment, and net export to the economic growth in ten provinces located in Sumatera Island. This research uses secondary data in form of combination data from cross section and time series data, in which the writer restricted the time of research from 2011 to 2014, it covers Regional Gross Domestic Products growth rate data, realization of capital expenditure, foreign investment data, domestic investment data, and net export data. The analysis method is regression panel data which is processed by fixed effect model. This research shows that variable of capital expenditure relates positively and does not significantly increase the economic growth, domestic investment relates negatively and contribute to the significant increase of economic growth, foreign investment relates negatively and does not have significant contribution to the economic growth, and net export relates positively and has a significant contribution to the economic growth in those ten provinces in Sumatera Island. Keywords: Economic growth, Panel Data, Capital Expenditure, Domestic and Foreign Investment, and Net Export.